Medium-Term Determinants of Current Accounts in Industrial and Developing Countries : An Empirical Exploration - Chinn, Menzie (IMF Working Papers; Working Paper ;, 2000)
This paper provides an empirical investigation of the medium-term determinants of current accounts for a large sample of industrial and developing countries. The analysis is based on a structural approach that highlights the roles of the fundamental macroeconomic determinants of saving and investment. Cross-section and panel regression techniques are used to characterize the properties of current account variation across countries and over time. Current account balances are positively correlated with government budget balances and initial stocks of net foreign assets. Among developing countries, measures of financial deepening are positively correlated while indicators of openness to international trade are negatively correlated with current account balances.